Balance ability, balance confidence and health-related quality of life among the elderly in a community in Chai Badan district, Lop Buri province - Charoensuksiri, Siripich; Charoensuksiri, Khemmapak; Uankeao, Apisuda (Journal of Medicine and Health Sciences, 2022)
Abstract An elderly person experiences changes in physiology, causing degenerative physical changes that affect their activities in terms of daily living or social participation. An objective of this study was to determine balance ability, balance confidence, and the health-related quality of life among the elderly in a community in Chai Badan district, Lop Buri province. This study was a cross-sectional research using purposive sampling. All of the participants were elderly people in a community in Chai Badan district, Lop Buri province. The research instruments included a demographic data questionnaire, a single leg stance test for static balance, a Timed Up and Go test for dynamic balance, an activities-specific and balance confidence scale (Thai version), and EQ-5D-5L (Thai version) and were analyzed using descriptive statistics. The results found that the participants consisted of 377 people, with 247 females and 130 males. The mean age was 68.60 ± 6.64 years old and the mean body mass index (BMI) was 24.11 ± 3.99 kg/m2. The majority of the participants had underlying diseases, namely hypertension and diabetes mellitus. According to the results, the balance ability results revealed that the majority of males and females had static and dynamic balance problems. The balance confidence test results revealed that participants had the most confidence when sweeping the floor and the least confidence on an escalator without holding the handrail. Regarding EQ-5D-5L, the results also found that the majority of the participants had no problems with the topics of mobility, self-care, usual activities, and anxiety/depression, whereas they had slight problems regarding the topic of pain/discomfort. This research study may be useful for public health personnel in planning policies and rehabilitation management, as well as organizing recreational activities, social activities, and activities promoting physical health in accordance with the context of each community.